MAIN FACTORS OF INCREASING SPIRITUALITY OF YOUTH IN THE CONDITIONS OF NEW UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article analyzes the main factors of increasing the spirituality of youth in the conditions of New Uzbekistan. The essence of the ongoing reforms in the formation of a harmoniously developed, spiritual, moral and physical healthy generation is revealed. The cooperation between the family and the educational institution in the upbringing of young people has been investigated.